(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article deals with the basic mechanisms of lexical-semantic derivation method of urbanonyms of Kriviy Rig. Attention is focused on transonymization and onymization. During the process of transonymization the transition of proper names occurs from one category to another. The names of the city linear objects (hodonyms) are indicative in this regard. Proper names are used in the form of the genitive case singular (genitive type with endings a, и, -oї, -ого). Basically, the genitive case singular is a distinctive feature of those names which are memorial ones. The names, which have an indeclinable word of foreign origin in their structure, are formed by the same principle. The owners of industrial production, administrative and domestic trade and commercial establishments use this way of forming proper names rather actively. In this case material form of expression which exists in onym space without any modifications (writing is used with quotes) transferred to urbanonymic space. Onymization characterizes the names of the linear and scaled intra city objects of various structural and grammatical organizations. Due to the onymization urbanonyms are formed from both abstract and concrete common nouns. As facts evidence, the most popular is metaphorical onymization, during which the metaphorical transfer involves the existence of a common semantic element: differential and connotative seme. Usually the work of trade and commercial structures, as well as the goods and services included in it are transferred onto the name (e.g. diadem – jewelry that is worn on the head, “Diadem” – jewelry store). The connection of the meaning of the forming stem with a derivative one can be quite weak, and the perception of a context – hypothetical.